Journeys of Emancipation, Struggle, or Both? Accounts from Professional Egyptian Migrant Women in Germany - Eddouss, Adam (AUC Knowledge Fountain, 2026)
This thesis explores the migration experiences of a group of professional Egyptian migrant women living in Germany. By employing a qualitative approach, primarily through semi-structured interviews, and guided by migration literature, this research attempts to move away from the oversimplistic approach that migration is an ‘either or’ reality. Mainstream migration scholarship, specifically that focusing on migrant women, tends to focus on depicting migration within an emancipation-struggle binary, presenting migrant women either as victims or as heroines. This work, antithetically, describes how migrant women experiences can be complex, highlighting, both instances of strength and struggle. Grounded in the words of the participants, this thesis presents their migration motivations, the challenges they face as migrants in Germany, and the positive impact that their migration journeys have on them. Along the way, this thesis emphasizes how gender and social norms act as a significant motivating factor of migration for professional Egyptian migrant women and how that is tightly interconnected with other economic, personal, and political motivations. Towards the end, this work also aims at depicting the transnational identities that these migrant women develop through migration and how these identities are dynamic, temporal, and changing in nature. Finally, this thesis highlights some of these migrant women’s future dreams and aspirations, emphasizing their ‘on-holdness’ and their delays due to migration management bureaucracies.